Dietary Protein Supplementation Helps in Muscle Thickness Regain after Abdominal Wall Reconstruction for Incisional Hernia. Issue 3 (March 2020) - Crocetti, Daniele; Carbotta, Giovanni; Cantelli, Fabio; Iorio, Olga; Gurrado, Angela; Sibio, Simone; Brauneis, Stefano; Cavallaro, Giuseppe
A modern approach to incisional hernia is oriented toward midline restoration to re-establish abdominal wall physiology and to restore muscular strength. A high-protein diet has been demonstrated to improve muscle function and mass. The aim of this prospective study was to evaluate the effect of a high-protein diet on abdominal muscle remodeling in patients submitted to abdominal wall reconstruction (AWR). Forty-five patients submitted to elective AWR were prospectively divided into two groups depending on pre- and postoperative daily protein assumption: Group A patients were submitted to a standard 2300 kcal diet with 103 g of protein intake (males) and 1800 kcal diet with 80 g of protein intake (females) starting one month before surgery and lasting for three months postoperatively; Group B patients were submitted to the same dietary regimen plus 34 g of purified proteins daily. Patients underwent ultrasound scan preoperatively and three and six months after surgery, to evaluate the widest thickness of the rectus abdominis muscle on the transverse umbilical line. Three patients reporting hernia recurrence were excluded. No significant difference among the two groups in muscle thickness growth after surgery was observed at three months after surgery, even if a favorable trend in Group B was noted (10% vs 19%, P = not significant). At six months after surgery, Group B patients showed a significant difference in muscle thickening (13% vs 32%, P < 0.05). The study demonstrates a positive effect of a protein diet on the rectus abdominis muscle thickening after AWR. Further studies are needed.